Organoid-Transplant Model Systems to Study the Effects of Obesity on the Pancreatic Carcinogenesis in vivo - Lupo, Francesca; Piro, Geny; Torroni, Lorena; Delfino, Pietro; Trovato, Rosalinda; Rusev, Borislav; Fiore, Alessandra; Filippini, Dea; De Sanctis, Francesco; Manfredi, Marcello; Marengo, Emilio; Lawlor, Rita Teresa; et al. (Frontiers in Cell and Developmental Biology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is the third leading cause of cancer-related mortality among adults in developed countries. The discovery of the most common genetic alterations as well as the development of organoid models of pancreatic cancer have provided insight into the fundamental pathways driving tumor progression from a normal cell to non-invasive precursor lesion and finally to widely metastatic disease, offering new opportunities for identifying the key driver of cancer evolution. Obesity is one of the most serious public health challenges of the 21st century. Several epidemiological studies have shown the positive association between obesity and cancer-related morbidity/mortality, as well as poorer prognosis and treatment outcome. Despite strong evidence indicates a link between obesity and cancer incidence, the molecular basis of the initiating events remains largely elusive. This is mainly due to the lack of an accurate and reliable model of pancreatic carcinogenesis that mimics human obesity-associated PDAC, making data interpretation difficult and often confusing. Here we propose a feasible and manageable organoid-based preclinical tool to study the effects of obesity on pancreatic carcinogenesis. Therefore, we tracked the effects of obesity on the natural evolution of PDAC in a genetically defined transplantable model of the syngeneic murine pancreatic preneoplastic lesion (mP) and tumor (mT) derived-organoids that recapitulates the progression of human disease from early preinvasive lesions to metastatic disease. Our results suggest that organoid-derived transplant in obese mice represents a suitable system to study early steps of pancreatic carcinogenesis and supports the hypothesis that inflammation induced by obesity stimulates tumor progression and metastatization during pancreatic carcinogenesis.